Three-phase five-level CHB inverter fed induction motor for renewable applications - G. V. V. Nagaraju; G. Sambasiva Rao (Institute of Advanced Engineering and Science, 2020)
This paper presents the three-phase CHB inverter fed induction motor suitable for renewable energy source applications. Normally, all present existing multilevel inverters produce multilevel output, but the number of components required is more, bulk in size, more in cost. Which are more burdens to small capacity renewable sources. These challenges are eliminated in CHB inverter. This CHB mainly consisting of one DC source, one capacitor and eight switches in each phase. To generate a five-level output in phase to ground voltage, it is required to maintain the capacitor voltage (V2) at fifty percent of the DC source voltage (V1). This capacitor voltage is regulated by a sensor less voltage regulating technique. The sensor less voltage regulation works without any sensor devices. We can implement this technique with very less cost compared to other techniques. The sensor less voltage regulation is realized by level-shifted sinusoidal pulse width modulation. The simulation results show a very good dynamic performance. Controller maintains the capacitor voltage at fifty percent of the source voltage irrespective of main source voltage changes and load changes. Inverter generates a five-level wave at the output from line to ground and seven-level wave from line to line with fewer Harmonic. It is implemented in matlab/simulink and showing good dynamic performance.